Hubungan antara Komorbiditas dan Mortalitas dengan Analisis Survival pada Pasien Kanker Payudara Stadium IV di RSUD Dr. Soetomo - Cahyani, Maria Benedictin Sandhi; Purba, Abdul Khairul Rizki; Wihandono, Asdi; Purwaningsih, Sri (Universitas Kristen Krida Wacana, 2026)
Breast cancer is a major global health concern, having the highest prevalence and ranking fifth in cancer-related mortality worldwide. However, data regarding mortality among breast cancer patients with and without comorbidities remain limited. Therefore, this study aimed to determine the association between comorbidities and mortality, as well as to analyze the survival of stage IV breast cancer patients at Dr. Soetomo General Hospital during the period 2020–2022. This study employed an observational analysis with a retrospective case–control design. Bivariate statistical analyses were performed using the Chi-square test, Fisher’s exact test, and the Mann–Whitney U test. Survival analysis was performed using the Kaplan–Meier method and the log-rank test. There were 271 samples that met the inclusion criteria. The majority of patients were early elderly (46–55 years old) and female. Based on the Charlson Comorbidity Index (CCI), most patients had severe comorbidities with a CCI score ≥ 5 (65,7%), and 48,3% of patients experienced mortality. The results showed a significant association between comorbidities and mortality in stage IV breast cancer patients (ρ = 0,00), with survival probability decreasing over time (ρ = 0,00). Patients without comorbidities had a higher probability of survival compared to those with comorbidities.